2004
DOI: 10.1189/jlb.0304127
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous ligands of Toll-like receptors

Abstract: Extensive work has suggested that a number of endogenous molecules such as heat shock proteins (hsp) may be potent activators of the innate immune system capable of inducing proinflammatory cytokine production by the monocyte-macrophage system and the activation and maturation of dendritic cells. The cytokine-like effects of these endogenous molecules are mediated via the Toll-like receptor (TLR) signal-transduction pathways in a manner similar to lipopolysaccharide (LPS; via TLR4) and bacterial lipoproteins (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
489
4
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 639 publications
(509 citation statements)
references
References 81 publications
7
489
4
9
Order By: Relevance
“…24 Other candidates include low molecular weight hyaluronan and fibrinogen from degraded extracellular matrix, as well as heat-shock proteins from necrotic cells. 25 A similar role of TLR4 was revealed in a murine myocardial ischemia reperfusion model in which TLR4 KO suffered smaller infarctions than TLR2 KO mice. 14,26 In contrast, the parenchyma TLR2 was an important initiator of inflammatory responses leading to renal dysfunction and kidney IRI.…”
Section: Discussionmentioning
confidence: 67%
“…24 Other candidates include low molecular weight hyaluronan and fibrinogen from degraded extracellular matrix, as well as heat-shock proteins from necrotic cells. 25 A similar role of TLR4 was revealed in a murine myocardial ischemia reperfusion model in which TLR4 KO suffered smaller infarctions than TLR2 KO mice. 14,26 In contrast, the parenchyma TLR2 was an important initiator of inflammatory responses leading to renal dysfunction and kidney IRI.…”
Section: Discussionmentioning
confidence: 67%
“…In the case of extracellular PAMPs, one of the major sensors is TLRs 74,75 As PAMPs and DAMPs both have adjuvant and inflammatory properties one possibility is that they actually work through the same receptors 74 . A potential role for TLRs has been explored so far primarily in inflammatory responses stimulated by dead cells and selected DAMPs (Table I).…”
Section: Receptors For Dampsmentioning
confidence: 99%
“…Ability of heat shock proteins to elicit a wide range of immunological effects has instigated scientific community in finding cell surface receptors for these molecules. It has been shown that the heat shock proteins mediate these immunological effects by binding with specific receptors like CD14, Toll like receptor 2 and 4 and CD91 [24,25].…”
Section: Heat Shock Proteins In Intercellular Signaling and Antigen Pmentioning
confidence: 99%